Are passengers less willing to pay for flying turboprops? An empirical test of the "turbo aversion hypothesis". (October 2018) - Marques Junior, Carlos Higino; Eller, Rogéria de Arantes Gomes; Oliveira, Alessandro V.M.
Abstract: Turboprop airplanes are known for their fuel efficiency on short-haul routes and thus naturally have a competitive advantage over jets in regional air transport. In Brazil, however, the market share of turboprops has considerably decreased in regional routes since the early 2010s. One possible explanation for this trend is the "turbo aversion hypothesis" (TAH), in which passengers dislike flying in turboprops, making carriers in regional markets more prone to operate either regional or smaller narrow-body jets based on demand-side economics. We empirically test this hypothesis by employing an econometric model of air travel demand in Brazilian regional markets. We find strong evidence rejecting the TAH, suggesting that the cost-side economics of the falling fuel prices apparently fully explains the observed erosion of the turboprop participation in the market. Highlights: We examine the issue of passenger aversion related to turboprop airplanes. We empirically investigate the behavior of demand in the regional air travel markets of Brazil via an econometric model. We test if passengers facing a higher participation of turboprop airplanes have lower willingness-to-pay for flights. We do not find any evidence that turboprop aircraft operations increase the market price elasticity of demand.